ENERGY CONSUMPTION AND ECONOMIC GROWTH: THE CASE OF POST-SOVIET ERA CENTRAL ASIAN COUNTRIES (Third Sector Social Economic Review, 2020)
The aim of this study is to estimate the impact of energy use, employment, and capital formation on real GDP for four Central Asian countries: Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan using panel data analysis between 1990 to 2018. This study uses ARDL[1] approach to investigate the long-run relationship among real GDP and energy use, employment, and capital formation. The results show an inverse relationship between real GDP and energy use, but a positive relationship real GDP and other independent variables, employment and capital formation. The Dolado-Lütkepohl Causality Test has been applied to determine the causality among the variables. Test results show that electric consumption increases real GDP. A unidirectional causality has been found between capital formation and real GDP. The results also show a unidirectional causality between capital and employment, confirming capital accumulation is a vital factor in economic growth. [1] The Autoregressive Distributed Lag
Keywords: Economic development; regional economics; energy use; capital formation